Redefining the Relationship: Palliative Care in Critical Perinatal and Neonatal Cardiac Patients - Natasha S. Afonso; Margaret R. Ninemire; Sharada H. Gowda; Jaime L. Jump; Regina L. Lantin-Hermoso; Karen E. Johnson; Kriti Puri; Kyle D. Hope; Erin Kritz; Barbara-Jo Achuff; Lindsey Gurganious; Priya N. Bhat (MDPI AG, 2021)
Patients with perinatal and neonatal congenital heart disease (CHD) represent a unique population with higher morbidity and mortality compared to other neonatal patient groups. Despite an overall improvement in long-term survival, they often require chronic care of complex medical illnesses after hospital discharge, placing a high burden of responsibility on their families. Emerging literature reflects high levels of depression and anxiety which plague parents, starting as early as the time of prenatal diagnosis. In the current era of the global COVID-19 pandemic, the additive nature of significant stressors for both medical providers and families can have catastrophic consequences on communication and coping. Due to the high prognostic uncertainty of CHD, data suggests that early pediatric palliative care (PC) consultation may improve shared decision-making, communication, and coping, while minimizing unnecessary medical interventions. However, barriers to pediatric PC persist largely due to the perception that PC consultation is indicative of "giving up." This review serves to highlight the evolving landscape of perinatal and neonatal CHD and the need for earlier and longitudinal integration of pediatric PC in order to provide high-quality, interdisciplinary care to patients and families.